Assessing Fiscal Sustainability in Indonesia - Nur Widiastuti; Ardyanto Fitrady; Tri Widodo (Jurnal Ekonomi dan Studi Pembangunan, 2023)
Fiscal sustainability is a concern in many economies, especially with increasing government debt in many countries, including Indonesia. This study aims to analyze fiscal sustainability in Indonesia for the 1970-2018 period. There are two methods to measure fiscal sustainability: testing the stationarity of government debt using government budget constraints and estimating fiscal sustainability using the fiscal reaction function. Error Correction Model is used to estimate the fiscal reaction function. The fiscal sustainability test with the debt stationarity test and the fiscal reaction function had consistent results, indicating fiscal sustainability in Indonesia. The government responded well to the increase in debt by increasing the primary surplus. This study proves that the relationship between debt and primary balance is not linear or quadratic. It shows that initially, the government responds to an increase in debt by increasing its primary surplus. However, at a certain threshold, the government’s ability to respond will weaken, so the government needs to pay attention and maintain the size of the government debt ratio towards Gross Domestic Product with fiscal discipline and fiscal reform through strict regulations and prudent debt management. However, strict debt regulations can limit economic growth. Therefore, an accurate threshold calculation is needed to determine the maximum debt to encourage optimal economic growth.